Penulisan Berita Dakwah Serta Efektivitas Penyampaian Informasi Islam - Musliadi Musliadi; Muhlis Muhlis (LP2M IAI Muhammadiyah Sinjai, 2022)
This paper aims to find out how the technique of reporting and writing da'wah news and opportunities for the effectiveness of Islamic information delivery. The research method used by the author is a qualitative method with the type of library research or library research. Literature study is research that uses various types of material in collecting data and information that the author collects through reading through documents, encyclopedias, dictionaries, journals, magazines, books, and so on from libraries. which has previously been carried out and has relevance to the theme or discussion as the basis for the researcher to obtain the basis for enriching the author's uniqueness on the theoretical basis used. The results of the research show that, in covering da'wah news, a reporter must collect Islamic data and information by looking for newspaper clippings, papers, or newspaper articles. and at the same time meeting journalistic technical standards, the opportunity to convey Islamic information in the digitalization era in this century is very likely to change the ummah from one situation to another that is better in all fields, realizing Islamic teachings in everyday life for an individual, family, group or group. the masses and for the life of society as a whole system of living together in the context of the development of the nation and of mankind. Keywords: Effectiveness of Islamic Information Delivery